2015
DOI: 10.1182/blood-2015-02-629543
|View full text |Cite
|
Sign up to set email alerts
|

The mTORC1 inhibitor everolimus has antitumor activity in vitro and produces tumor responses in patients with relapsed T-cell lymphoma

Abstract: • The mTOR pathway is constitutively activated in the TCL cells and is responsible for TCL proliferation.• This is first trial to demonstrate that mTORC1 inhibitors (everolimus) have substantial antitumor activity (44% overall response rate) in patients with relapsed TCL.Everolimus is an oral agent that targets the mammalian target of rapamycin (mTOR) pathway. This study investigated mTOR pathway activation in T-cell lymphoma (TCL) cell lines and assessed antitumor activity in patients with relapsed/refractory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
86
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 101 publications
(89 citation statements)
references
References 37 publications
0
86
0
3
Order By: Relevance
“…Of interest, rapamycin analogues, which disrupt the mTORC signaling cascade have shown promise in early phase clinical trials of PTCL patients. [4951]…”
Section: Discussionmentioning
confidence: 99%
“…Of interest, rapamycin analogues, which disrupt the mTORC signaling cascade have shown promise in early phase clinical trials of PTCL patients. [4951]…”
Section: Discussionmentioning
confidence: 99%
“…6 We have demonstrated that the PI3K/mTOR pathway is activated in NHL cells 10,11 and that mTORC1 inhibitors have single-agent activity in relapsed B-cell 12 and T-cell NHL. 13 Everolimus has also been shown to be safe and effective when combined with rituximab in relapsed DLBCL patients. 14 Inhibition of the pathway at the PI3K level is effective and idelalisib is now approved for relapsed CLL and indolent B-cell NHL.…”
Section: Introductionmentioning
confidence: 99%
“…Everolimus, an mTORC1 inhibitor, was investigated as a monotherapy in T-NHL cell lines and in the setting of a phase II study in 16 relapsed T-cell lymphomas. Results demonstrated significantly inhibited proliferation of malignant T cells, translating into 43% PR in MF patients [39,73]. Subsequent studies with everolimus as monotherapy or as a combination with immune checkpoint blockade or other drugs would be a rational next step.…”
Section: Mtor Inhibitorsmentioning
confidence: 99%